RNAi Technology: A New Path for the Research and Management of Obligate Biotrophic Phytopathogenic Fungi - Padilla-Roji, Isabel; Ruiz-Jimenez, Laura; Bakhat, Nisrine; Vielba-Fernández, Alejandra; Pérez-García, Alejandro; Fernández-Ortuño, Dolores (MDPI, 2023)
Powdery mildew and rust fungi are major agricultural problems affecting many economically important crops and causing significant yield losses. These fungi are obligate biotrophic parasites that are completely dependent on their hosts for growth and reproduction. Biotrophy in these fungi is determined by the presence of haustoria, specialized fungal cells that are responsible for nutrient uptake and molecular dialogue with the host, a fact that undoubtedly complicates their study under laboratory conditions, especially in terms of genetic manipulation. RNA interference (RNAi) is the biological process of suppressing the expression of a target gene through double-stranded RNA that induces mRNA degradation. RNAi technology has revolutionized the study of these obligate biotrophic fungi by enabling the analysis of gene function in these fungal. More importantly, RNAi technology has opened new perspectives for the management of powdery mildew and rust diseases, first through the stable expression of RNAi constructs in transgenic plants and, more recently, through the non-transgenic approach called spray-induced gene silencing (SIGS). In this review, the impact of RNAi technology on the research and management of powdery mildew and rust fungi will be addressed.
Keywords: Interacciones ARN; Plantas transgénicas; Microbiología agrícola; Hongos fitopatógenos; RNA interference; VIGS; HIGS; ATM-HIGS; dsRNA; SIGS; Transgenic plants; Powdery mildew; Rust